Correlation of microscopic grain evolution in post‐CdCl2 annealing and performance of CdS/CdTe thin‐film solar cells fabricated using pulsed laser deposition. Issue 12 (31st August 2016) - Zeng, Guanggen; Harrison, Paul; Kidman, Ali; Al‐mebir, Alaa; Feng, Lianghuan; Wu, Judy
Abstract : The effect of post annealing in CdCl2 was investigated to elucidate the correlation between the evolution of the microstructure of CdTe thin films with the annealing time and the performance of CdS/CdTe thin‐film solar cells made by in situ pulsed laser deposition (PLD). It has been found that the crystallinity of the annealed film is improved considerably as the CdTe polycrystalline grains evolved into grain clusters with a dendrite structure. While longer annealing time allows larger grain size, the increased film surface roughness outweighs the benefit of the improved crystallinity, resulting in increased structural disorders, such as pinholes. In fact, the concentration of the pinholes was found to increases monotonically with annealing time when it exceeds the optimal value, resulting in degradation of device performance and yield especially when pinholes appeared near the CdS/CdTe interface. This result illustrates the importance of controlling the microstructure of CdTe film and its interface with CdS to high‐performance CdTe/CdS thin‐film solar cells.